KEJAHATAN SEKSUAL DAN HUKUM ISLAM - Achmad Thorik; Maula nida (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
Sexual crimes have many types and terms. In addition, cultural differences can create different perceptions of sexual crimes. This article discusses how western views and Islamic views detail the types of sexual crimes. This study uses a philosophical normative approach, comparative analysis method, and qualitative research methods of literature in fiqh and zawajir books. Then the results are compared with various types of sexual crimes in Western terms. Through it, the meeting points and differences between the two views made clear and solutions to understanding unwritten Islamic law. It is important for adherents of these two views to understand each other before having a dialogue on deeper themes. Keywords: Sexual crimes; Islamic law; western law